Improving Yield and Quality of Processing Potato Crops Grown in the Argentinian Pampas: the Role of N, P and S and Their Impact on CO2 Emissions - Caldiz, Daniel Osmar; Viani, P.G.; Giletto, Claudia Marcela; Zamuner, Ester Cristina; Echeverria, Hernan Eduardo (Springer Netherlands, 2018)
The area grown with processing potato crops in the Argentinian Pampas has been increasing steadily since 1995. The aim of this work was to assess the effects of N, P and S upon yield and tuber quality and their impact on CO2 emissions assessed with the Cool Farm Tool-Potato. During the spring-summer growing seasons 2008/2009 and 2009/2010, ten fertilization experiments to individually assess N, P and S effects were carried out in the southeast region of the Argentinian Pampas. Nitrogen (four N rates), phosphorus (four P rates) and sulfur (three S rates) were applied at planting and tuber initiation; at combined rates of 0, 50, 100 and 150 kg N ha−1, and at rates of 0, 25, 50 and 100 kg P ha−1 and 0, 10 and 20 kg S ha−1. N and P had a positive effect on total tuber yield, but tuber dry matter concentration (DMC) decreased at higher N rates. The fraction of marketable tubers suitable for processing into French fries increased with the addition of N, showed no variations with P fertilization, and decreased when S was applied. French fry colour, length/width (L:W) ratio and tuber defects were not affected by N, P and S fertilization. With regard to CO2 emissions assessed with the Cool Farm Tool-Potato, results showed that the higher the N rates the higher the CO2 emissions, but they decreased at higher yields. P and S rates did not have an impact on the CO2 emissions, which also decreased at higher yields. Under the production system of the Pampas, N should be split between planting and tuber initiation, and intermediate P rates should be applied all at planting, in order to improve crop yield and quality and to reduce CO2 emissions.